2007
DOI: 10.1038/ng1953
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish miR-214 modulates Hedgehog signaling to specify muscle cell fate

Abstract: Numerous microRNAs (miRNAs) have been discovered in the genomes of higher eukaryotes, and functional studies indicate that they are important during development. However, little is known concerning the function of individual miRNAs. We approached this problem in zebrafish by combining identification of miRNA expression, functional analyses and experimental validation of potential targets. We show that miR-214 is expressed during early segmentation stages in somites and that varying its expression alters the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
240
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(248 citation statements)
references
References 22 publications
7
240
0
1
Order By: Relevance
“…45 Not surprisingly, PMOs have also proven to be effective anti-miRNA compounds in Zebrafish. Flynt et al 46 reported knockdown of miR-214 in Zebrafish, demonstrating a role for this miRNA in muscle cell development. Like PNAs, neutral PMOs are difficult to use with mammalian cells.…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…45 Not surprisingly, PMOs have also proven to be effective anti-miRNA compounds in Zebrafish. Flynt et al 46 reported knockdown of miR-214 in Zebrafish, demonstrating a role for this miRNA in muscle cell development. Like PNAs, neutral PMOs are difficult to use with mammalian cells.…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…2B). We also co-injected antisense morpholinos complementary to miR-203 (i.e., miR-203 MO ) that function to block the activity of endogenous miR-203 and thus should lead to increased fluorescence (31,33). As a control, GFP lacking the lef1 3Ј UTR also was injected into single-cell zebrafish embryos with and without exogenous miR-203 and miR-203 MO (Fig.…”
Section: Figmentioning
confidence: 99%
“…Western Blot Analyses. At 1 dpf, embryos were dechorionated, deyolked, and sonicated in lysis buffer as described previously (33). Then Ϸ30 embryos were pooled, and one-sixth of the resultant volume was loaded into each lane (Fig.…”
Section: Figmentioning
confidence: 99%
“…Recent studies have shown that miRNAs are aberrantly expressed in different cell types and at different developmental stages, suggesting that miRNAs play important roles in cell growth (8)(9)(10)(11)(12), differentiation (13,14), metabolism (15), and programmed cell death (16). Moreover, previous studies have demonstrated that a number of miRNAs are also involved in tumor pathogenesis and the development of different types of human cancers, including cervical (17), ovarian (8,18), lung (19), breast (9), colon (10), and prostate cancers (12).…”
Section: Introductionmentioning
confidence: 99%
“…miR-214 was first explored for its role in apoptosis (20). Later, several studies documented that miR-214 is involved in the murine aging process (21), modulates Hedgehog signaling to specify muscle cell fate (14), and induces cell survival and cisplatin resistance by targeting PTEN in human ovarian cancer (8). However, the role of miR-214 in cervical cancer cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%